Gut Microbiota and Related Electronic Multisensorial System Changes in Subjects With Symptomatic Uncomplicated Diverticular Disease Undergoing Rifaximin Therapy - De Vincentis, Antonio; Santonico, Marco; Del Chierico, Federica; Altomare, Annamaria; Marigliano, Benedetta; Laudisio, Alice; Reddel, Sofia; Grasso, Simone; Zompanti, Alessandro; Pennazza, Giorgio; Putignani, Lorenza; Guarino, Michele Pier Luca; et al. (Frontiers in Medicine, 2021)
Background. Intestinal dysbiosis might play a pathogenetic role in subjects with symptomatic uncomplicated diverticular disease (SUDD), but the effect of Rifaximin therapy has been scantly explored with regard to gut microbiota variations in patients with SUDD. Aims. To verify to which extent Rifaximin treatment affects the gut microbiota and whether an electronic multisensorial assessment of stools and breath has the potential for detecting these changes. Methods. Breath and stool samples were collected from consecutive patients with SUDD before and after a 7 days’ therapy with Rifaximin. Stool microbiota was assessed, and the electronic multisensorial assessment was carried out by means of the BIONOTE electronic (e-)tongue in stools and (e-)nose in breath. Results. Forty-three subjects (female 60%, median age 66 years) were included, and 20 (47%) reported clinical improvement after Rifaximin therapy. Alpha and Beta diversity of stool microbiota did not significantly change after treatment, while a significant variation of selected taxa was shown (i.e. Citrobacter, Coprococcus, Anaerotruncus, Blautia, Eggerthella lenta, Dehalobacterium, SMB53 and Haemophilus parainfluenzae). Overall, the electronic multisensorial system suboptimally mirrored microbiota changes, but it was able to efficiently predict patients’ clinical improvement after Rifaximin with accuracies ranging from 0.81 to 0.98. Conclusions. In patients with SUDD, Rifaximin administration is associated with significant variation of selected taxa. While inaccurate in predicting gut microbiota change, an electronic multisensorial system, made up of e-tongue and e-nose, was able to predict clinical improvement, thus potentially qualifying as an easy and cheap tool to forecast subjects taking most likely benefit from Rifaximin therapy.